Report on the evaluation of the network "asialand/sloping lands". Of the international board for soil research and management (IBSRAM) - Bianchi, G.; Geiser, U.; Grieder, C. (Bern (Suiza), 1993)
Sumario (En)
Ilus., 43 ref.
Keywords: SUELO; DIFUSION DE INFORMACION; INVESTIGACION; MANEJO DEL SUELO; SOSTENIBILIDAD